Developing an implementation plan for a career development program in small manufacturing businesses in Bloemfontein - Motlogelwa, Itumeleng Pedro (North-West University, 2018)
In the current global market, businesses whether large or small, have competitors regardless of the industry. (Kunins, 2010:14). To remain competitive, it is important for businesses to leverage on, among other issues, the workforce as a competitive weapon (Miller, 2009:51). Businesses can utilise the workforce to gain competitive advantage by introducing career development programs. Career development is the series of activities or the on-going/lifelong process of developing one’s career. It usually refers to managing one’s career in an intra-organizational or inter-organizational scenario. The implementation of career development programs helps organisations to retain best workforce. This study is based on the assessment of implementation of employees’ career development plans in small manufacturing businesses in Bloemfontein. The objective of the study is to assess the implementation of employees’ career development plans in small manufacturing businesses in Bloemfontein, with the focus on providing recommendations to enhance effective implementation of employees’ career development plans. A literature review was conducted to explore the impact of implementation factors. The six implementation factors and readiness factors were reviewed. A questionnaire constructed used to measure the importance of implementation factors, according to the respondents. A target group of 60 employees was identified and questionnaires were distributed to them. A total of 59 questionnaires were returned and all of them were deemed usable for the study. The validity of each variable was individually determined by the calculation of the Cronbach Alpha coefficient. Conclusions and recommendations for favourable conditions which will enhance a successful implementation of employees’ career development plans were made based on the empirical data obtained.
MBA, North-West University, Potchefstroom Campus, 2018
Keywords: Employees’ career development plan; Career development; Career Development programs; Employees’ development